2017
DOI: 10.1021/acs.est.7b04994
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unknown Antiandrogenic Compounds in Surface Waters by Effect-Directed Analysis (EDA) Using a Parallel Fractionation Approach

Abstract: Among all the nuclear-receptor mediated endocrine disruptive effects, antiandrogenicity is frequently observed in aquatic environments and may pose a risk to aquatic organisms. Linking these effects to responsible chemicals is challenging and a great share of antiandrogenic activity detected in the environment has not been explained yet. To identify drivers of this effect at a hot spot of antiandrogenicity in the German river Holtemme, we applied effect-directed analysis (EDA) including a parallel fractionatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 58 publications
2
46
0
1
Order By: Relevance
“…For secondary fractionation, an aliquot of the primary fraction F18 corresponding to 3 L of water equivalent was concentrated into 2 mL of methanol:water (30:70), and aliquots of 400 µL were fractionated using an aminopropyl column (Unison NH2, 150 × 10 mm, 3-µm particle size, Imtakt) with methanol [B]:water [A] as mobile phases, both containing 0.1% formic acid. Aminopropyl has been identified in a previous study as a stationary phase highly orthogonal to C18 in RP chromatography (Muschket et al 2018). Gradient elution was carried out with a flow rate of 2.8 mL/min.…”
Section: Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…For secondary fractionation, an aliquot of the primary fraction F18 corresponding to 3 L of water equivalent was concentrated into 2 mL of methanol:water (30:70), and aliquots of 400 µL were fractionated using an aminopropyl column (Unison NH2, 150 × 10 mm, 3-µm particle size, Imtakt) with methanol [B]:water [A] as mobile phases, both containing 0.1% formic acid. Aminopropyl has been identified in a previous study as a stationary phase highly orthogonal to C18 in RP chromatography (Muschket et al 2018). Gradient elution was carried out with a flow rate of 2.8 mL/min.…”
Section: Fractionationmentioning
confidence: 99%
“…In a previous study, Weiss et al (2009) demonstrated that fractionation of complex mixtures may eliminate such masking effects. Combining effect-based monitoring and fractionation with chemical analysis of active fractions in effect-directed analysis (EDA) is a powerful tool to identify the drivers of endocrine disruption (Thomas et al 2004;Brack et al 2016;Hashmi et al 2018;Muschket et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these compounds were 7-diethylamino-4-methylcoumarin, 7-ethylamino-4-methylcoumarin and 7-amino-4-methylcoumarin, which were recently identified at this site as causative compounds for the observed anti-androgenicity [40]. The latter is used as optical brightener (or fluorescent whitening agent) for textiles and a constituent in cleaning detergents and washing powders [27] and has not been found anywhere else in surface water or wastewater [36].…”
Section: Site H2 (Holtemme Downstream Of Wwtp Silstedt)mentioning
confidence: 99%
“…Furthermore, it may involve mixture toxicity modeling, and finally hazard confirmation, which should account for effects at higher levels of biological organization, such as populations and communities under realistic exposure conditions [10]. The power of this approach has been demonstrated, e.g., for anti-androgenic effects detected in vitro in a small river in Germany impacted by treated wastewater [43]. Parallel fractionation with different stationary phases together with testing and chemical screening of the resulting fractions was able to reduce the number of candidate peaks to very few peaks, eventually identifying and confirming the fluorescent dye coumarin 47 as the driver of the measured effect in vitro and in vivo in Medaka embryos.…”
Section: Effect-directed Analysismentioning
confidence: 99%